Psychometric evaluation of the Persian version of the Rosenberg Self-Esteem Scale among medical sciences students - Abbasi, Ali; Moradkhani, Ahmadreza; Shahri, Bahar; Khosravi, Hamed; Sohrabi, Atena; Mirhosseini, Seyedmohammad (Frontiers in Psychology, 2024)
Introduction The present research carried out to assess the psychometric properties of the Persian version of the Rosenberg Self-Esteem Scale (RSES) among medical sciences students. Methods This methodological study took place at Shahroud and Semnan Universities of Medical Sciences in Iran. A sample of 380 medical sciences students was selected through convenience sampling. The study assessed face and content validity, and maximum likelihood explanatory factor analysis (MLEFA) was performed. To evaluate the proposed model by MLEFA, confirmatory factor analysis was carried out. Reliability was examined using Cronbach's alpha coefficient, McDonald's omega, and the intra-class correlation coefficient. Results The students had an average age of 22.49 ± 2.72 years. The maximum likelihood explanatory factor analysis (MLEFA) divided the RSES into two components: positive self-esteem and negative self-esteem, which together explained 50.7% of the total variance. Confirmatory factor analysis showed that the model fit the observed data well. The resulting subscales exhibited high internal consistency and stability. Conclusion The findings of the current study indicate that the Persian version of the Rosenberg Self-Esteem Scale possesses acceptable validity and reliability among Iranian medical sciences students.